Alternatif Alat Bantu KPU Selain Sirekap - W, Wahyudinsyah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to examine the KPU's policy in using SIREKAP as a tool by providing another alternative to the KPU's objectives, namely that the KPU can use other information technology media to publish the results of voting and vote counting at the polling station level, not just SIREKAP. Methods Research methods, empirical law (non-doctrinal), case and policy approaches, data collection using documentation, observation and interviews and combining with literature review of legal documents relevant to the object under study, and analyzed descriptively. The research found that Sirekap, which was widely criticized by the Indonesian people, was predicted to be a tool, but was not actually a tool and even made things difficult, created differences in views, and created problems during the publication of the results of the count and recapitulation in stages. Sirekap as a publication media that shows transparency should be able to use alternative social media such as Facebook, Instagram, Websites, and others that can publish images or videos.